1992
DOI: 10.1002/tea.3660290204
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual difficulties experienced by senior high school students of electrochemistry: Electric circuits and oxidation‐reduction equations

Abstract: The purpose of this research was to investigate students' understanding of electrochemistry following a course of instruction. A list of conceptual and propositional knowledge statements was formulated to identify the knowledge base necessary for students to understand electric circuits and oxidation‐reduction equations. The conceptual and propositional knowledge statements provided the framework for the development of a semistructured interview protocol which was administered to 32 students in their final yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
4
16

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 18 publications
7
127
4
16
Order By: Relevance
“…In the meantime, the ninth-grade students scored lowest on the items related to concepts in electricity, a finding which corresponds to the many studies that reveal that electricity concepts are difficult for children to learn, especially the concepts of circuit, current, and electrical energy (Shipstone, 1988;Garnett & Treagust, 1992;Furio & Guisasola, 1998). We discovered two common misconceptions regarding electricity in our study, which have also been revealed by many researchers (Magnusson, Boyle & Templin, 1997;Osborne, 1983;Russell, 1980;Shipstone, 1984): Students thought that the bulb in a series nearest the positive electrode would light first (Appendix, item 18), and that two bulbs together use more electricity than a single bulb (Appendix, item 17).…”
Section: Discussionsupporting
confidence: 57%
“…In the meantime, the ninth-grade students scored lowest on the items related to concepts in electricity, a finding which corresponds to the many studies that reveal that electricity concepts are difficult for children to learn, especially the concepts of circuit, current, and electrical energy (Shipstone, 1988;Garnett & Treagust, 1992;Furio & Guisasola, 1998). We discovered two common misconceptions regarding electricity in our study, which have also been revealed by many researchers (Magnusson, Boyle & Templin, 1997;Osborne, 1983;Russell, 1980;Shipstone, 1984): Students thought that the bulb in a series nearest the positive electrode would light first (Appendix, item 18), and that two bulbs together use more electricity than a single bulb (Appendix, item 17).…”
Section: Discussionsupporting
confidence: 57%
“…However, many students find the diverse models that are used to explain science challenging and confusing (Bent, 1984;Carr, 1984;Garnett & Treagust, 1992;Gilbert & Boulter, 2000) although some researchers (Russell, Kozma, Jones, et al1997) advocate that learning with diverse models prevents students developing alternative conceptions that are hard to change. This problem is particularly severe for young students and for those students whose abstract reasoning is poorly developed.…”
Section: Student Modelling Abilitymentioning
confidence: 99%
“…Les diffi cultés sur le déplacement des porteurs de charges (Garnett & Treagust, 1992) sont gérées par des représentations au niveau microscopique.…”
Section: • Piles Et éLectrolyseursunclassified